Enhancement of Photoconversion Efficiency of ZnO Nanorod-Based Dye-Sensitized Solar Cells in Presence of ZrO2 Thin Energy Barrier - Koo, Gumae; Lee, Wonjoo; Kil, Byungho; Ahn, Heejoon; Cho, Byung Won; Han, Sung-Hwan (AMER SCIENTIFIC PUBLISHERS, 2011)
In order to enhance the power conversion efficiency of ZnO nanorods-based dye-sensitized solar cells (DSSCs), ZrO2 thin energy barriers were formed on ZnO nanorods using a sol-gel method. In DSSCs, the short-circuit current was substantially increased, and the dark current was significantly reduced in the presence of the ZrO2 layer. Due to suppressed recombination in the presence of the ZrO2 layer, 81.3% increment of power conversion efficiency is achieved compared to those without ZrO2 layer.
Keywords: QUANTUM DOTS; RECOMBINATION; DEPOSITION; PEDOTPSS